1989
DOI: 10.1128/jcm.27.7.1543-1547.1989
|View full text |Cite
|
Sign up to set email alerts
|

Direct identification of Mycobacterium tuberculosis, Mycobacterium avium, and Mycobacterium intracellulare from amplified primary cultures in BACTEC media using DNA probes

Abstract: San Diego, Calif.) directed at the Mycobacterium tuberculosis complex and Mycobacterium avium-M. intracellulare complex were used to identify acid-fast bacilli directly from specimens grown in BACTEC 12B bottles (Becton Dickinson and Co., Towson, Md.). Clinical specimens were inoculated directly or after decontamination into a BACTEC 12B bottle, Middlebrook 7H11 agar, and Lowenstein-Jensen medium. Conventional media were incubated at 37°C in 5% C02 and examined weekly for 6 weeks. Identification of isolates gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(32 citation statements)
references
References 9 publications
0
32
0
Order By: Relevance
“…gordonae, and M . avium complex (MAC) which is composed of M. avium and M. intracellulare (Gen-Probe Inc., San Diego, CA) (10,14,16,17,19,33). The results of the sequence analysis were unknown when these conventional identifications were performed.…”
Section: Identification Of Mycobacterium Strains By Conventional Methodsmentioning
confidence: 99%
“…gordonae, and M . avium complex (MAC) which is composed of M. avium and M. intracellulare (Gen-Probe Inc., San Diego, CA) (10,14,16,17,19,33). The results of the sequence analysis were unknown when these conventional identifications were performed.…”
Section: Identification Of Mycobacterium Strains By Conventional Methodsmentioning
confidence: 99%
“…Accurate laboratory diagnosis is essential to ensure effective clinical management of infected patients [10][11][12][13][14]. The performance of participating laboratories with MOTT has improved over time.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, nucleic acid probes are being used for the identification of mycobacteria from positive cultures [10,11,[13][14][15][16]. The methods survey indicated that only 20% of respondents used molecular techniques to identify isolates of mycobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Disseminated M. terrae infection in a patient with advanced human immunodeficiency virus disease was recently reported (2).The identification of pathogenic versus nonpathogenic species is important for patient management, since treatment regimens for infection caused by one Mycobacterium species are often not effective against another.Conventional methods for species identification of mycobacteria mainly depend on morphological, cultural, and biochemical tests. These methods require diverse techniques and complex procedures that take a long time and yet the efficiency of identification is still limited (11,15). Other methods such as thin-layer chromatography (TLC) and high-performance liquid chromatography (HPLC) are more powerful, but are cumbersome, expensive and limited by the need for standardized growth conditions.…”
mentioning
confidence: 99%
“…Conventional methods for species identification of mycobacteria mainly depend on morphological, cultural, and biochemical tests. These methods require diverse techniques and complex procedures that take a long time and yet the efficiency of identification is still limited (11,15). Other methods such as thin-layer chromatography (TLC) and high-performance liquid chromatography (HPLC) are more powerful, but are cumbersome, expensive and limited by the need for standardized growth conditions.…”
mentioning
confidence: 99%